The Aesthetic Significance of Quranic Verse-Endings in Surah al-Dukhān: A Rhetorical Study - Al-Qahtani, Haya Fuhaid Saad (Arts for Linguistic & Literary Studies, 2025)
This study explores the aesthetic significance of Quranic verse-endings (fawāṣil) in Surah al-Dukhān, treating them as a dynamic structural element that shapes both semantic content and rhetorical rhythm. Using an integrative approach that combines phonetic, rhetorical, and contextual analysis, the research highlights how the fāṣilah functions as both an aesthetic and semantic device. After outlining the concept and importance of the verse-ending, the study examines two primary domains: the verse-endings of punishment scenes, characterized by auditory force and intensified awe, and those of mercy scenes, marked by softness and reassurance. The contrast underscores how sound and meaning interact to reinforce the thematic context. Since early Islamic scholarship, critics have recognized the unique stylistic role of Quranic verse-endings, noting that they transcend sajʿ and rhyme by fusing semantic depth with phonetic resonance. The findings further demonstrate that the verse-ending is deliberately constructed for rhetorical effect, employing strategies such as emphasis, explicitness, and antithesis. This study affirms that investigating Quranic verse-endings provides a significant pathway to understanding rhetorical inimitability and appreciating the enduring impact of Quranic discourse on the human soul.